ابنِ تیمیہ کا فقہی مقام اور استنباطِ احکام کے اصول؛ایک تجزیاتی مطالعہ: An analytical study of Ibn-e-Taymiyyah’s jurisprudential position and principles of elicitation rules - Fazal Haq, Muhammad (Al-Amīr Research Journal for Islamic Studies, 2021)
In Islamic jurisprudence, there are different degrees of inference and reasoning. He is also a mujtahid who, while respecting the principle of a particular religion, differs from his religion only in its branches and does not go against the principles of that particular religion. There is also a mujtahid who has jurisdiction over both the principles and the rules. Such a mujtahid is not a follower of any of the jurisprudential religions. Taqi-ud-Din Ahmad ibn Taymiyyah remarkable, recognized, and medieval Sunni Theologian, jurisconsult, logician, and great reformer today, he is known by the title of Sheikh-ul-Islam. In some sciences and arts, he had Ijtihadi abilities and practitioners. He did not spare a single minute in expressing his critical ability and competence according to his instincts in principles and disciplines. Ibn Taymiyyah’s critical ability and competence were manifested in the form of differences in the scientific world of the Islamic world. Due to this, Ibn Taymiyyah faced severe criticism from the academic circles all his life. In this article, it will be reviewed that Ibn Taymiyyah’s jurisprudential and doctrinal differences came to light based on ijtihad, principles and his jurisprudential position and status and method of derivation and reasoning of the issues.